Between Freedom and Captivity: A Dual Analysis of Pirates of the Caribbean: The Curse of the Black Pearl through Freudian Psychoanalysis and Postcolonial Criticism - Putra, Jonathan Syah; Aritonang, Jeshua Nathananael; Jeswin, Oliver Rafael; Riven, Abednego Rick; Wijaya, Josh Fitzkioshi (Jurnal Pendidikan Makarios, 2025)
This paper critically examines Pirates of the Caribbean: The Curse of the Black Pearl through the dual lenses of Freudian psychoanalytic theory and postcolonial criticism, revealing that the narrative articulates complex thematic oppositions through a multifaceted analysis. The study yields three key results: 1) Freudian constructs such as the ‘id,’ ‘ego,’ and ‘superego’ exemplify the internal conflicts of characters, emphasizing the dynamic tension between instinctual desires and moral control; 2) a clear binary opposition is established between the pursuit of freedom, embodied by characters like Captain Jack Sparrow, and the state of entrapment, exemplified by the cursed crew whose internalized guilt and consequences of greed bind them; and 3) the integration of psychoanalytic and postcolonial perspectives provides interdisciplinary insights, demonstrating how historical power dynamics and personal identity conflicts converge in cinematic storytelling. The significance of these findings lies in their potential to refine methodologies in literary and film criticism by offering a nuanced understanding of narrative complexity and cultural dynamics. Consequently, further research is expected to extend this dual-framework approach to a broader range of films and narrative forms, thereby enriching scholarly debates on themes of freedom, power, and identity within contemporary popular culture.